Health Related Quality of Life of Patients after Cardiac Surgery (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction:  Cardiovascular disease (CVD) is the primary cause of disability and morbidity in many developed countries around the world. But timely management with cardiac surgery can reduce the mortality.Objectives: To assess the health related quality of life (HRQOL) of the CVD patients after coronary artery bypass grafting (CABG).Materials and Methods:  This cross-sectional observational study was carried out among purposively selected CABG patients from January to December 2013. A total of 78 post CABG patients were interviewed with short form health survey (SF-36) questionnaire at different hospitals in Dhaka.Results: The study patients age ranged from 40 to 82 years and the proportion were higher among those of more than 60 years (38.5%) of age. Majority (48.7%) were educated up to HSC level. Explaining the characteristics of illness, the average duration of sufferings was 121.91±115.31 days and Post treatment duration in month was 14.97±19.25. The study findings showed a good level of QOL; with an average score of 78.2. The mental and physical components scores were 79.9 & 77.1 respectively. There were statistically significant (p